Risks for chronic non-communicable diseases in the view of Vigitel participants - Mássimo, Erika de Azevedo Leitão; Freitas, Maria Imaculada de Fátima (Saúde e Sociedade, 2014)
The aim of this study was to interpret reflexions of population groups divided by age on the risk of suffering from Chronic Non-Communicable Diseases (CNCDs) as part of the VIGITEL project qualitative axis, that monitors the prevalence of risk factors for CNCDs in Brazil. Methodological Procedures Data collection was conducted through focus groups sampled at Belo Horizonte, Minas Gerais, in 2008, considering that there is not, in similar studies, the need for validation by comprehensive sample. The interest is to deepen this subject so that it will be possible to compare it to other studies afterwards. Results Results showed that young people know the risks of CNCDs, but consider that living without taking risks is impossible. People from 31 to 50 years old are informed and become aware, but want to continue living without health concerns, negotiating with themselves their personal measures of risk. People above 51 years consider the risks of CNCDs inherent to the human condition, but they may grow larger due to an ‘unruly’ life; they are afraid and try to care for themselves searching for health care. Conclusions The reflexions of the groups show representations that highlight the impossibility of placing health constantly in the foreground, in everyday life. There is a desire to live pleasures and satisfactions which often are not consistent with the determination of being healthy. Moreover, there is the human need of transgressions to feel alive and stronger than death. Interdisciplinary approaches able to relativize the weight of these representations in order to incorporate healthy lifestyles, collectively and autonomously, are essential.